(untitled) (The International Journal for Scientific Research, 2024)
The study aimed to explore the role of renewable energy in achieving the goals of Saudi Arabia’s Vision 2030, and how ACWA Power can contribute to sustainable development through renewable energy projects. The study also sought to highlight the challenges faced in utilizing renewable energy in the Kingdom, the ways to overcome them, and the expected outcomes of implementing a renewable energy strategy in Saudi Arabia. The study adopted a descriptive-analytical approach and used a questionnaire tool to collect data. The results of the study revealed that renewable energy plays a significant role in achieving sustainable development in line with Saudi Vision 2030, with an average response score of 3.52, indicating the positive impact of renewable energy in this context. The study further emphasized that ACWA Power contributes significantly to sustainable development through its innovations and advanced technologies, as well as its future strategies inspired by the Kingdom’s Vision. ACWA Power also enjoys broad investment opportunities in light of the national direction to enhance renewable energy projects. In this context, the study recommended increasing investments in the renewable energy sector due to its importance in achieving sustainable development under Vision 2030. It also called for supporting innovations and advanced technologies by encouraging companies to develop and utilize new technologies. The study stressed the need to take advantage of the investment opportunities provided by Vision 2030 to enhance renewable energy investments, and to offer incentives for companies and investors to engage in this vital sector.